CHAIN ACCOUNT RESPONSES. - LOPER D (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Summary of the responses various industries and organizations would have to proposition 5. Mentions what their response would be and what they could be convinced to do in opposition to the bill.